Pendampingan Menguatkan Gerakan Literasi Sekolah di SMP dan SMA Al Umanaa Boarding School, Sukabumi - Supriatnoko; Mustofa, Anwar; Khairas, Eri Ester (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2023)
The Al Umanaa Foundation/Al Umanaa Modern Islamic Boarding School has implemented the School Boarding Movement at Yunior and Senior High Schools since 2016, and championed it as one of excellence. A form of seriousness is the holding of local literacy content subjects. Foundations/Islamic Boarding School define literacy as the ability to use language to read, write, listen, and speak. In the implementation of literacy learning at Yunior and Senior High Schools, among other things, they do not yet have literacy learning guidebook, they still need additional collections of non-learning books and there are not enough information boards available for students; written work, and there is no common understanding among teachers regarding literacy management and the role of library as a means of supporting literacy. The target of the service is to assist Yunior and Senior High Schools in strengthening the implementation of the school literacy movement. The implementation of this service uses the mentoring method and the Al Umanaa academic community participation method. The result of this activity is that teachers and librarians’ understanding of the management of the School Literacy Movement, after receiving technical guidance activities on literacy management, and regarding activities of library record and facilities, has become stronger, in sense that they can understand and be able to implement it in literacy learning activities. Next, the School Literacy Movement Guidebook at Yunior and Senior High School has already been produced and started to be used as a teachers’ guidebook in learning Literacy Subjects starting from the 2023/2024 academic year, non-textbook grants and literacy information boards created by students can be utilized by Al Umanaa Modern Islamic Boarding School community.